Transport properties of polymeric membranes - Thomas, Sabu; Wilson, Runcy; Anil Kumar, S.; George, Soney C. (Amsterdam Elsevier, 2018)
Transport Properties of Polymeric Membranes is an edited collection of papers that covers, in depth, many of the recent technical research accomplishments in transport characteristics through polymers and their applications. Using the transport through polymer membranes method leads to high separation efficiency, low running costs, and simple operating procedures compared to conventional separation methods. This book provides grounding in fundamentals and applications to give you all the information you need on using this method. This book discusses the different types of polymer, their blends, composites, nanocomposites and their applications in the field of liquid, gas and vapor transport. Some topics of note include modern trends and applications of polymer nanocomposites in solvent, vapor and gas transport; fundamentals and measurement techniques for gas and vapor transport in polymers; and transport properties of hydrogels. This handpicked selection of topics, and the combined expertise of contributors from global industry, academia, government and private research organizations, make this book an outstanding reference for anyone involved in the field of polymer membranes.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Polymers -- Transport properties; Polymeric composites -- Research; Transport theory; Nanocomposites (Materials); Electronic books